Pengaruh Kompos dan Takaran Teh Kompos terhadap Pertumbuhan dan Hasil Tanaman Sawi (Brassica juncea L.) di Lahan Kering - Veronika Abuk (Fakultas Pertanian, Universitas Timor, 2021)
The study aims to know the effects of compost onthe growth and productivity of mustard plants (Brassicajuncea L.) and toknowhowadoseofcompostteaeffectgrowthand productivity of the mustard. Thestudywascarried out in September and October of 2020 in the opposition of daughter Kimbana BTN, South Bikomi District, City Kefamenanu, North Central Timor (TTU). The research design used is a complete random design (CRD) of two distinct factors. The first factor compost consisting of thre cedars without compost as control, postfif teen ton/acresare, compost twenty five tons/acres are. These cond factoris a three-aras doseofcompost and compost tea two, compost five millits.The observed variable compost tea in general donot showthe effect of interactions on all observations.The sole impact of compost measure twenty five tons/acres are shows fresh, non-econimical data of the tallest plant real difference between the cedar’streatment. Compost tea two,fivemilli compost effects optimally increases growth and produce plants that are properly expressing with the freshet weigth of the tallest tatal plant, the higthest fresh weight.